CIFOR-ICRAF: Gender equity and social inclusion across the agri-food landscape - Garner, Elisabeth (CIFOR-ICRAF, 2023)
The Center for International Forestry Research and World Agroforestry (CIFOR-ICRAF) have long engaged with communities, focusing on people-first solutions to environmental challenges that threaten sustainable and equitable agri-food systems. CIFOR-ICRAF has identified inequality as one of the five global challenges to address strategically over the next 10 years. As a cross-cutting theme, gender equity and social inclusion (GESI) informs the way the organization works across all its activities, from forest and agroforestry landscapes to climate change policy and action to inclusive value chains. Central to its approach is the need to address the power dynamics that shape the unique experiences, barriers and opportunities of the diverse and intersecting identities of women, including indigenous peoples, youth, refugees, and other marginalized groups. Drawing on a deep and evolving understanding of the barriers to gender equality and inclusion, CIFOR-ICRAF conducts applied research to explore the dynamics of gender and other social categories in forestry and agroforestry landscapes. This presentation will discuss institutional efforts to mainstream gender equity and social inclusion by providing examples of research-led development projects across the institution, as well as the importance of centering justice and resilience in these efforts. The presentation will provide examples of previous efforts and discuss the future of the organization.